Changing the recognition specificity of a DNA-methyltransferase by in vitro evolution - Tímár, Edit (Oxford University Press, 2004)
The gene coding for the SinI DNA-methyltransferase, a modification enzyme able to recognize and methylate the internal cytosine of the GG(A)/(T)CC sequence, was subjected to in vitro mutagenesis, DNA-shuffling and a strong selection for relaxed GGNCC recognition specificity. As a result of this in vitro evolution experiment, a mutant gene with the required phenotype was selected. The mutant SinI methyltransferase carried five amino acid substitutions. None of these was found in the ‘variable region’ that were thought to be responsible for sequence specificity. Three were located near the N-terminal end, preceding the first conserved structural motif of the enzyme; two were found between conserved motifs VI and VII. A clone engineered to carry out only the latter two replacements (L214S and Y229H) displays relaxed recognition specificity similar to that of the parental mutant, whereas the clone carrying only the N-terminal replacements showed a much weaker change in recognition specificity. The enzyme with two internal mutations was purified and characterized. Its catalytic activity (k(cat)/K(m)) was ∼5-fold lower towards GG(A)/(T)CC and 20-fold higher towards GG(G)/(C)CC than that of the wild-type enzyme.